2019
DOI: 10.3390/ijerph16224456
|View full text |Cite
|
Sign up to set email alerts
|

The Development of Glaucoma after Surgery-Indicated Chronic Rhinosinusitis: A Population-Based Cohort Study

Abstract: This study investigates the development of glaucoma in subjects with surgery-indicated chronic rhinosinusitis (CRS) by the use of the National Health Insurance Research Database in Taiwan. Individuals that received the functional endoscopic sinus surgery (FESS) with a diagnostic code of CRS were regarded as surgery-indicated CRS and enrolled in the study group. Four non-CRS patients were age- and gender-matched to each patient in the study group. The exclusion criteria included legal blindness, ocular tumor, h… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 54 publications
(72 reference statements)
1
3
0
Order By: Relevance
“…Another study highlighted that surgery-associated CRS contributed to a significant risk ratio in both the open-angle glaucoma (adjusted HR = 2.244) and NTG (adjusted HR = 2.127) subgroups, but not in the angle-closure glaucoma subgroup. Consistently, the present investigation also demonstrated an increased risk ratio for incident NTG events in all CRS patients, with an adjusted HR of 1.41 over a 10-year follow-up period [19]. Moreover, several studies hypothesized that ostial obstruction in CRS could limit airflow, leading to hypoxia, which could contribute to retinal ischemia, a factor associated with glaucoma development [30][31][32].…”
Section: Discussionsupporting
confidence: 87%
See 1 more Smart Citation
“…Another study highlighted that surgery-associated CRS contributed to a significant risk ratio in both the open-angle glaucoma (adjusted HR = 2.244) and NTG (adjusted HR = 2.127) subgroups, but not in the angle-closure glaucoma subgroup. Consistently, the present investigation also demonstrated an increased risk ratio for incident NTG events in all CRS patients, with an adjusted HR of 1.41 over a 10-year follow-up period [19]. Moreover, several studies hypothesized that ostial obstruction in CRS could limit airflow, leading to hypoxia, which could contribute to retinal ischemia, a factor associated with glaucoma development [30][31][32].…”
Section: Discussionsupporting
confidence: 87%
“…Additionally, previous studies have shown that the respiratory distress condition is very closely correlated with increased intraocular pressure (IOP) [16,17]. Moreover, some cohort studies from Taiwan revealed a positive correlation between patients with CRS and the subsequent development of open-angle glaucoma [18,19].…”
Section: Introductionmentioning
confidence: 99%
“…On the other side, compressive lesion might be risk factor for OAG development in which the ocular adnexal lymphoma as well as infantile hemangioma and associated OAG have been reported previously [24,25]. Chronic rhinosinusitis contributes to elevated incidence of subsequent glaucoma in a population-based study [26]. Regarding NPC, orbital invasion occurred in a large number of patients [14,27].…”
Section: Discussionmentioning
confidence: 88%
“…1. Appendix Table A4, available at http://links.lww.com/OPX/A658, shows the characteristics of the remaining 45 related studies 12–56 . Two of the 45 articles were conducted from the same cohort 44,45 .…”
Section: Resultsmentioning
confidence: 99%